If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -9x = 105 + -30x Solving 6 + -9x = 105 + -30x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '30x' to each side of the equation. 6 + -9x + 30x = 105 + -30x + 30x Combine like terms: -9x + 30x = 21x 6 + 21x = 105 + -30x + 30x Combine like terms: -30x + 30x = 0 6 + 21x = 105 + 0 6 + 21x = 105 Add '-6' to each side of the equation. 6 + -6 + 21x = 105 + -6 Combine like terms: 6 + -6 = 0 0 + 21x = 105 + -6 21x = 105 + -6 Combine like terms: 105 + -6 = 99 21x = 99 Divide each side by '21'. x = 4.714285714 Simplifying x = 4.714285714
| 3x+12=x+72 | | x+3x+5x-6=180 | | 3a-8a=11a | | x^5y^4/x^3y^6 | | 3n^2-16n+21=0 | | a/15+5=4 | | -40-9x=214-44x | | 1150+15x=y | | x+2+3x=57 | | 66-22x=3x+6 | | 10(x+12)=-70 | | 9-x=6 | | z^2+8*z+17=0 | | 2(x-3)+5(x+4)=4(-2x-3)-3(x+4) | | -3+8b=-187 | | 7r-8r= | | 15x^4-21x+240=0 | | y=0.7(200-133) | | 15x^4-105x+240=0 | | 56=(7/8)y | | y=0.7(200-0) | | 3x-1(4/x+1) | | 3x-1((1/x+1)(4)) | | 49n^2+56n+12=0 | | 4m^8-4m^4+9=0 | | 0.85x+10=50.00 | | 0.85x+10=50 | | 5x(x-4)+3x=120-4x | | (x^2-1)(0)= | | -3/4*x=4*1/2 | | x(x+1)-3=12 | | A=3(2a-5)-(6-2a)+(3a+1)2 |